Differential Elimination of Anti-Thymocyte Globulin of Fresenius and Genzyme Impacts T-Cell Reconstitution After Hematopoietic Stem Cell Transplantation - Oostenbrink, Lisa V. E.; Jol-van der Zijde, Cornelia M.; Kielsen, Katrine; Jansen-Hoogendijk, Anja M.; Ifversen, Marianne; Müller, Klaus G.; Lankester, Arjan C.; van Halteren, Astrid G. S.; Bredius, Robbert G. M.; Schilham, Marco W.; van Tol, Maarten J. D. (Frontiers in Immunology, 2019)
Anti-thymocyte globulin (ATG) is a lymphocyte depleting agent applied in hematopoietic stem cell transplantation (HSCT) to prevent rejection and Graft-versus-Host Disease (GvHD). In this study, we compared two rabbit ATG products, ATG-Genzyme (ATG-GENZ) and ATG-Fresenius (ATG-FRES), with respect to dosing, clearance of the active lymphocyte binding component, post-HSCT immune reconstitution and clinical outcome. Fifty-eigth pediatric acute leukemia patients, (n=42 ATG-GENZ, n=16 ATG-FRES), who received a non-depleted bone marrow or peripheral blood stem cell graft from an unrelated donor were included. ATG-GENZ was given at a dosage of 6-10 mg/kg; ATG-FRES at 45-60 mg/kg. The active component of ATG from both products was cleared at different rates. Within the ATG-FRES dose range no differences were found in clearance of active ATG or T-cell re-appearance. However, the high dosage of ATG-GENZ (10 mg/kg), in contrast to the low dosage (6-8 mg/kg), correlated with prolonged persistence of active ATG and delayed T-cell reconstitution. Occurrence of serious acute GvHD (grade III-IV) was highest in the ATG-GENZ-low dosage group. These results imply that dosing of ATG-GENZ is more critical than dosing of ATG-FRES due to the difference in clearance of active ATG. This should be taken into account when designing clinical protocols.